2006
DOI: 10.1074/jbc.m603324200
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Positive Feedback Phosphorylation of Mixed Lineage Kinase 3 by JNK Reversibly Regulates Its Distribution to Triton-soluble Domains

Abstract: MLK3 (mixed lineage kinase 3) is a widely expressed, mammalian serine/threonine protein kinase that activates multiple MAPK pathways. Previously our laboratory used in vivo labeling/mass spectrometry to identify phosphorylation sites of activated MLK3. Seven of 11 identified sites correspond to the consensus motif for phosphorylation by proline-directed kinases. Based on these results, we hypothesized that JNK, or another proline-directed kinase, phosphorylates MLK3 as part of a feedback loop. Herein we provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 67 publications
3
38
0
Order By: Relevance
“…The increased levels of active JNK and active ERK observed (Supplementary Figure 3), upon treatment with the p38 inhibitor, likely reflect the previously reported antagonistic crosstalk between the p38 pathway and other MAPKs (Hall and Davis, 2002;Schachter et al, 2006), as this phenomenon was also observed in MDA-MB-231 cells (Supplementary Figure 4). (-) or with 25 nM AP21967 and subjected to a transwell migration assay as described under Materials and methods.…”
Section: Mlk3 Signaling In Breast Cancermentioning
confidence: 60%
See 1 more Smart Citation
“…The increased levels of active JNK and active ERK observed (Supplementary Figure 3), upon treatment with the p38 inhibitor, likely reflect the previously reported antagonistic crosstalk between the p38 pathway and other MAPKs (Hall and Davis, 2002;Schachter et al, 2006), as this phenomenon was also observed in MDA-MB-231 cells (Supplementary Figure 4). (-) or with 25 nM AP21967 and subjected to a transwell migration assay as described under Materials and methods.…”
Section: Mlk3 Signaling In Breast Cancermentioning
confidence: 60%
“…In complementary experiments, we asked whether induced expression of active MLK3 could promote the migration of poorly invasive MCF-7 breast cancer cells (Zhang et al, 2004;Schachter et al, 2006) and MCF10A mammary epithelial cells. When a stable population of MCF-7-MLK3 cells was treated with the transcriptional inducer AP21967 and subjected to a transwell migration assay, a 2.5-fold increase in the migration of the MCF-7 cells ( Figure 4a) was observed.…”
Section: Mlk3 Signaling In Breast Cancermentioning
confidence: 99%
“…However, transcriptional-level feedback is not the only option for MAPK pathways: the JNK pathway is also subject to feedback phosphorylation. It is known that MLK3 and DLK can be directly phosphorylated by activated JNK to exert positive feedback, although the exact sites and mechanisms differ greatly between these two proteins (44,96). Such positive feedback loops can result in bistable switches (97) that can ensure immediate and robust responses by rapid, local, and maximal kinase activation.…”
Section: Phosphatases and Feedback Mechanisms In Control Of Jnk Activitymentioning
confidence: 99%
“…5A); however, the underlying mechanism is unclear. It was suggested that positive feedback phosphorylation of MLK3 by JNK may lead to sustained JNK activation (Schachter et al, 2006), which may result in amplification of oxidative stress. We observed decreased ROS production in APAPtreated MLK3-KO mice, compared with WT mice (Fig.…”
Section: Mlk3 In Apap-induced Liver Injurymentioning
confidence: 99%